Forests in the context of climate change in Kazakhstan - Jenniver Sehring (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2012)
Being a country with very low forest cover, forests are usually not in the focus of research and strategies of natural resource management in Kazakhstan. Nevertheless, forests play an important ecological role, especially in maintaining conditions for agriculture and hydrological regimes. The paper gives a description of the state of the resource and the administrative regulations on forestry in Kazakhstan. It outlines the impacts of climate change on forestry and the potential role of forests in adaption and mitigation are described. Finally, it takes stock of current forest policies, which are less based on climate change considerations but on the country's green growth strategy.
Keywords: 330